Design and synthesis of a novel photoaffinity ligand for the dopamine and serotonin transporters based on 2 beta-carbomethoxy-3 beta-biphenyltropane - Newman, Amy Hauck; Cha, Joo Hwan; Cao, Jianjing; Kopajtic, Theresa; Katz, Jonathan L.; Parnas, M. Laura; Vaughan, Roxanne; Lever, John R. (AMER CHEMICAL SOC, 2006)
Tropane-based photoaffinity ligands covalently bind to discrete points of attachment on the dopamine transporter (DAT). To further explore structure-activity relations, a ligand in which the photoactivated group was extended from the 3-position of the tropane ring was synthesized from cocaine via a Stille or Suzuki coupling strategy. 3-(4'-Azido-3'-iodo-biphenyl-4-yl)-8-methyl-8-aza-bicyclo[3.2.1] octane-2-carboxylic acid methyl ester (11; K-i = 15.1 +/- 2.2 nM) demonstrated high binding affinity for the DAT. Moreover, this compound showed moderate binding affinity for the serotonin transporter (SERT, K-i = 109 +/- 14 nM), suggesting the potential utility of [I-125] 11 in both DAT and SERT protein structure studies.
Keywords: UPTAKE INHIBITORS COCAINE; IRREVERSIBLE LIGANDS; BINDING; AFFINITY; ANALOGS; RECOGNITION; BENZTROPINE; MAZINDOL